OPTIMASI PERSEDIAAN SPAREPART PADA PT XYZ MENGGUNAKAN TEKNIK SPARE PART QUANTITY DETERMINATION - Jonny, Jonny (Industrial and Systems Engineering Assessment Journal (INASEA), 2014)
PT XYZ, an Indonesian public company, is one of cement producers in Indonesia. In order to produce good quality of cements, it designed manufacturing processes with good quality of facilities. One of its processes is burning process using rotary kiln with temperature up to 1,450 Â°C that may cause deterioration due to thermal expansion. Therefore, it should be coated by fire bricks as its spare parts. In general, a fire brick is built to withstand high temperature with low thermal conductivity. It also has such a limited useful life so that having excessive stocks may elevate costs, while running out of stock may cause the production to stop running. In order to keep the production running well, the company intuitively placed orders with additional 37.5% to its requirements. However, this technique has caused excessive stock levels and financial burdens. Therefore, the company has initiated an improvement initiative to optimize its stock. After conducting in-depth observation and comprehensive research, the company found that by using Spare Part Quantity Determination, it can reduce its inventory cost by 28.05% from previously inventory cost up to IDR 3.058 million to IDR 2.2 million per year.